Coercion and Disunity as Tremors in African Nationhood Foundation: Armah and Kourouma’s Fault Line Criticisms: Array - Njoku, Anthony (Acta Universitatis Danubius. Relationes Internationales, 2021)
Africa of the twenty first century is plagued by a horde of social and economic misfortunes traceable to both political and historical evolutions which have taken the people back to the beginning of everything African. Two of them, important events, are the foundation of African nationhood which has led to heated debates; and disunity which is partly inherent and instinctual and partly the outcome of the former. Sequel to this, the present paper provides answers to questions such as: how did the African nationhood evolve? What role did disunity play both in the formative and later stages of African nationhood? It goes about this quest by studying the impact of the Berlin Conference of 1884 on Africa and that of wars on Africa’s Ancient empires. It is a qualitative research based on the works of Ayi Kwei Armah and Ahmadou Kourouma and review of criticism of external influence on the constitution of the African nationhood and its consequential role in the post-independence dilemma. In the end, the paper concludes that the foundation of African nationhood is faulty as a result of imposition and coupled with lack of unity among African ethnicities which constitutes a source of malaise. Armah and Kourouma might have x-rayed historical facts to the best of their abilities, yet there is element of tribal sentiment that characterizes their accounts, and which also to an extent is aporetic.